ANALISIS FAKTOR-FAKTOR DAYA TARIK WISATA BALI DAN IMPLIKASINYA TERHADAP PERENCANAAN PARIWISATA DAERAH BALI - SURADNYA, I MADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006)
This policy research focuses on exploring the factors that attract foreign tourists to visit Bali and to discuss its implications on planning of Bali as a tourism destination. At the moment the tourism development planning is mainly based on the supply side, that is the resources available in the region. However, due to the increase of competition and the demanding tourists more comprehensive planning base involving the demand side, i.e. expectations of the visitors are becoming of equally important for the success of the tourism planning itself. A survey was conducted and 505 visitors from the main tourist generating countries who visited Bali during peak and low season visit in 2005 participated the survey. The respondent were randomly selected when they were at the waiting room at the Ngurah Rai Airport before leaving the country. The factor analysis successfully explored 8 factors that attract foreign visitors to visit Bali, e.i. (1) Reasonable price of tourism products, (2) Cultural attractions, (3) Beach attractions, (4) Convenience traveling, (5) Relaxing environment, (6) Image of Bali as a tourist destination, (7) Natural beauty, and (8) Hospitality of local people. Based on the research findings, it is strongly recommended that in developing Bali as a world class tourist destination, the tourism planner should consider those factors in the planning process in order to better serve the more demanding tourists and the increase of competition among tourist destinations.
Keywords: Factors, Attraction, Tourists, Visitingi